Implementation of Policy on The Results of Monitoring and Evaluation of Public Information Disclosure: Case Study on Regional Government Organization of Banten Province - Hilman, Hilman (Indonesian Association for Public Administration (IAPA), 2024)
The implementation of information disclosure in public bodies is a mandate of Law Number 14 of 2008 concerning Public Information Disclosure which applies to all public bodies, both in the central government through ministries and other state institutions and regional governments through regional apparatus organizations or regional apparatus work units. The importance of monitoring and evaluating the implementation of the law for regional apparatus in order to ensure that public information services are periodic, at all times, and immediately, and information that is excluded can run well. The research data was taken from the results of monitoring and evaluation activities in 2023 by the Banten Information Commission on 39 regional apparatus organizations. Through a qualitative approach, the data is processed and described according to data from indicators I, II, III, and IVnamely website development, public information development, public information services, and provision of public information. The results of the monitoring and evaluation show that of the 39 public bodies, there are 25 public bodies that are Informative, 9 are approaching informative, 2 are quite informative, and 3 are less informative. This confirms that the majority of regional apparatus organizations are already informative by implementing public information service standards that refer to PERKI 1 of 2021.However, in the future, Information and Documentation Management Officers in Regional Government Organizations still need to maximize services for public information requests for applicants and users of information whose numbers continue to increase. Therefore, monitoring and evaluation of public bodies need to be continuously maintained in terms of quantity and quality by the information commission.